Organizational behavior I = Essential theories of motivation and leadership - Miner, John B. (M.E. Sharpe, 2005)
This comprehensive text provides a detailed review and analysis of the building-block theories in Organizational Behavior. Expanding on his previous work in the field, John Miner has identified the key theories that every student or scholar needs to understand to be considered literate in the discipline.